Comparison of Analgesic Requirement and Pain Intensity in Lower Segment Cesarean Section (LSCS) with Ketofol and Conventional Induction of General Anesthesia - Misbah Siddique Khosa, Aisha Siddiqa, Syeda Taskeen Ejaz, Mirza Shakeel Ahmad, Muhammad Abdul Aziz, Syed Aushtar Abbas Naqvi, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: to compare the analgesic requirement and pain intensity in LSCS with ketofol and conventional induction of general anesthesia Study Type: randomized controlled trial Study Place and Duration: department of Anesthesiology at Ghazi Medical College & Teaching Hospital, Dera Ghazi Khan, from 1st January 2019 to 30th June 2019. Material and methods: 100 adult participants (20–40 years) ASA physical status 1 and 2, with no previous case of neurologic or cardiovascular undergoing LSCS operations were enlisted in a randomised prospective comparative study after receiving approval from the ethical research committee. Patients were divided into two groups, each with 50 patients: group P (propofol) and group KP (ketamine) (ketofol). The surgeon picked a closed envelope as the method of randomization. Visual analogue scale was used to assess the postoperative pain where, 0 means no pain, 1-3 means mild pain, 4-7 means moderate pain, and 8-10 means severe pain using a visual analog scale, where 0 means no pain, 1-3 means mild pain, 4-7 means moderate pain, and 8-10 means severe pain. Furthermore, the need for postoperative analgesia was examined, including the need for fentanyl. Results: The majority of the patient's Group P and Group KP had 0 VAS scoresof28 (56.0%) and 26 (52.0%), respectively, (p=0.475). Intra operation fentanyl was required 3 (6.0%) in Group P and 1 (2.0%) in Group PK, (p=0.307). While, post-operation fentanyl was required 7 (14.0) in Group P and 4 (8.0) in Group PK, (p=0.338). Conclusion: Ketofol as an induction agent can be used as an alternative which is relatively safe and show less side effects in comparison to propofol alone. Keywords: Ketamine, propofol, ketofol, pain intensity, analgesia requirement, conventional induction, general anesthesia